Papel do receptor B2 das cininas e da NADPH-oxidase no dano secundário associado ao traumatismo cranioencefálico em camundongos - Ferreira, Ana Paula de Oliveira (2013)
Traumatic brain injury (TBI) is a major cause of death and disability. This condition results in neurological and cognitive impairment. In this context, it has been demonstrated that bradykinin, the main metabolite of the kallikrein-kinins system is involved in the increased permeability of the blood-brain barrier, in edema formation and leukocyte accumulation induced by TBI. Experimental findings also indicate an connection between kinin receptors and the activity of the enzyme nicotinamide adenine dinucleotide phosphate (NADPH)-oxidase, an enzyme that produces superoxide radical. It is known that the kalikrein-kinin and NADPH-oxidase activity participate of neuroinflammation triggered by TBI. However, few studies have evaluated their effects on the development of posttraumatic cognitive impairment. Hence, the present study evaluated the role of kinin receptors (B1 and B2) and the NADPH-oxidase inhibitor (apocynin)in neuromotor deficits, memory impairment, cortical lesion volume, oxidative and inflammatory damage induced by moderate lateral fluid percussion injury in mice. Therefore, we determined the effects of kinin receptors antagonists (des - Arg9-[Leu8]-bradykinin and HOE-140) and apocynin injected subcutaneously 30 min 24 hours post trauma. The present study demonstrated that both, HOE-140 and apocynin, protected against memory impairment triggered by trauma, but showed no effects in motor dysfunction caused by TBI. It should be noted that memory improvements was not due to nonspecific effects over the memory test, because the pharmacological treatment used in this study did no alter locomotor and/or anxiety-like behavioral. Treatment with HOE-140 also attenuated the NADPH-oxidase activity, reinforcing the connection between the B2 receptor and this enzyme. Moreover, both treatments attenuated the ipsilateral cortex inflammation (levels of interleukin-1β, tumoral necrosis factor-α and nitric oxide metabolites) and oxidative damage (lipid peroxidation, protein carbonylation and inhibition of Na+, K+ ATPase) induced by tested model. On the other hand, only treatment with HOE-140 reduced the cerebral edema. The results presented in this study suggest that kinins, through of the B2 receptor and possibly through NADPH-oxidase, are involved in neuroinflammation and oxidative stress caused by trauma. Moreover, it is plausible that excessive activation of B2 receptors and subsequent activation of the enzyme NADPH-oxidase facilitate the cortical lesion progression resulting in deterioration of object recognition memory.